2020
DOI: 10.1007/s11517-020-02211-y
|View full text |Cite
|
Sign up to set email alerts
|

Sound transmission in human thorax through airway insonification: an experimental and computational study with diagnostic applications

Abstract: Pulmonary diseases and injury lead to structural and functional changes in the lung parenchyma and airways, often resulting in measurable sound transmission changes on the chest wall surface. Additionally, noninvasive imaging of externally driven mechanical wave motion in the chest (e.g., using magnetic resonance elastography) can provide information about lung stiffness and other structural property changes which may be of diagnostic value. In the present study, a comprehensive computational simulation (in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
10
0
2
Order By: Relevance
“…9 Recently, the utility of a breath sound analysis as a simple, safe, and noninvasive lung function test has been studied, and technological progress in this field has been remarkable. 10,11 Clinically, current reports have suggested that new breath sound analyses can be used in the clinical evaluation of airway changes, 12 and have evaluated an assessment of airway obstruction using breath sound analyses in children. 13 The possibility to objectively evaluate the airway condition in infants has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recently, the utility of a breath sound analysis as a simple, safe, and noninvasive lung function test has been studied, and technological progress in this field has been remarkable. 10,11 Clinically, current reports have suggested that new breath sound analyses can be used in the clinical evaluation of airway changes, 12 and have evaluated an assessment of airway obstruction using breath sound analyses in children. 13 The possibility to objectively evaluate the airway condition in infants has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in breath sound analyses have been remarkable 10,11) . In clinical practice, attempts have been made to use breath sound analyses for the obstructive evaluation of airway narrowing 23,24) , and the technique is improving 18,22) .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the utility of a breath sound analysis as a simple, safe and non-invasive lung function test has been studied, and technological progress in this field has been remarkable 10,11) . Clinically, current reports have suggested that new breath sound analyses can be used in the clinical evaluation of airway changes 12) , and have evaluated the lung function using breath sound analyses in children 13) .…”
Section: Introductionmentioning
confidence: 99%
“…At this band, the thorax model is established and verified by simulations and experiments, see [30,31]. The feasibility of diagnosing pulmonary diseases using sound at this band is also researched, see [32,33]. Sound of frequency between 1 and 10 kHz is hard to permeate thorax.…”
Section: Introductionmentioning
confidence: 99%